FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI MINYAK SAWIT DI INDONESIA - Rafidah Rafidah; Hijri Juliansyah; Murtala Murtala; Noviami Trisniarti; Depin Aprillia (LPPM Universitas Malikussaleh - Indonesia, 2022)
This study aims to analyze the factors that influence the production of palm oil in Indonesia . This study uses panel data, which is a combination of 7-year time series data and 23 provinces of cross section data from during 2014 to 2020. To analyze the data, this uses panel data analysis methods. Based on technique model selection, the best choices model in study is fixed effects models . The results showed from the partial test of the three independent variables, land area, labor and the number of palm oil processing companies have a positive and significant effect on palm oil production in Indonesia. Further more, The simultaneously results showed that. the area of land, the number of workers, the number of palm oil processing companies have a positive and significant effect on palm oil production in Indonesia